Strategi Dinas Kependudukan dan Pencatatan Sipil dalam Percepatan Aktivasi Identitas Kependudukan Digital (IKD) di Kota Surabaya - Azka Kharisma Putri Imada; Firli Imansa Syafirlana; Kharimatun Nisa; Lia Meylani Widyawati; Rheanda Abi Aufa (Journal of Governance Innovation, 2025)
City of Surabaya as the second largest metropolitan area in Indonesia has implemented e-Government to support government digitalization. One of the manifestations is the Digital Population Identity or Identitas Kependudukan Digital (IKD), which is regulated in Minister of Internal Affairs Regulation Republic of Indonesia Number 72 of 2022. The action to accelerate the activation of IKD in Surabaya continues to be intensified on the grounds that the availability of KTP blanks is running low, the readiness of service digitization must be improved, and increase community awareness of the usefulness of IKD. The purpose of this study is to identify and analyze Population and Civil Registration Agency or Disdukcapil's strategy in accelerating the activation of IKD in Surabaya and the obstacles in accelerating the current IKD activation. This research uses a descriptive qualitative method that presents data based on the results of interviews, observations, and also documentation. The results showed that the strategy carried out by Disdukcapil in encouraging the acceleration of IKD activation in the community is very good because the services provided are not only carried out 'in the office' but there are also active methods of going directly to the community which are considered more effective in attracting public interest in IKD activation. For the future, the functions and features of IKD must be expanded in order to increase the practicality of the community to get more efficient services in their respective fields of management.